2022
DOI: 10.1007/s10479-022-04867-1
|View full text |Cite
|
Sign up to set email alerts
|

Decision optimization in cooperation innovation: the impact of big data analytics capability and cooperative modes

Abstract: Data-driven innovation enables firms to design products that are more responsive to market needs, which greatly reduces the risk of innovation. Customer data in the same supply chain has certain commonality, but data separation makes it difficult to maximize data value. The selection of an appropriate mode for cooperation innovation should be based on the particular big data analytics capability of the firms. This paper focuses on the influence of big data analytics capability on the choice of cooperation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 86 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…In addition, digital transformation makes data and information key factor inputs for enterprise production, and the data and information elements substantially improve the accuracy and effectiveness of factor resource allocation decisions throughout the enterprise and play a significant role in promoting the supervision of management to regulate their behavior and subjective judgments during the decision-making process or even in distorting the space for manipulation [78,79]. With improvements in big data capability, the gap between the innovation performance of enterprises in loose and tight modes increase significantly [80] to improve the level of corporate governance. The improvement in corporate governance has a multiplier effect on green technology innovation and the efficient production of enterprises.…”
Section: Corporate Governance (Cgo) Channelmentioning
confidence: 99%
“…In addition, digital transformation makes data and information key factor inputs for enterprise production, and the data and information elements substantially improve the accuracy and effectiveness of factor resource allocation decisions throughout the enterprise and play a significant role in promoting the supervision of management to regulate their behavior and subjective judgments during the decision-making process or even in distorting the space for manipulation [78,79]. With improvements in big data capability, the gap between the innovation performance of enterprises in loose and tight modes increase significantly [80] to improve the level of corporate governance. The improvement in corporate governance has a multiplier effect on green technology innovation and the efficient production of enterprises.…”
Section: Corporate Governance (Cgo) Channelmentioning
confidence: 99%
“…We find that most existing research on digital technology considers improving market demand through blockchain technology. Furthermore, there are several researchers investigating the implications of big data and artificial intelligence on supply chains, such as Ji et al (2022), Wu et al (2022), and Xu et al (2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of BDAC on supply chain innovation has also been addressed in the literature: using a case study, Tan et al (2015) concluded that BDAC helps in understanding how different functional areas or different sub-companies can develop different ways of working together thus optimizing new product manufacturing and development processes. Recently, Jaouadi (2022) discovered BDAC positively impacts the innovation occurring in the supply chain, and Ji et al (2022) examined the role of BDAC in cooperative innovation processes among firms in the supply chain, concluding it is essential to enhancing performance.…”
Section: Big Data Analytics Capability and Innovation Capabilitymentioning
confidence: 99%